DIGITAL TRANSFORMATION AND ITS INFLUENCE ON CUSTOMER SATISFACTION AND BUSINESS PERFORMANCE - Khairulla Fayzullaevich Sattarov (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
This paper examines the role of digital transformation as a critical driver of organizational success in the modern business environment. It highlights how digital technologies enhance customer satisfaction through personalization, real-time interaction, and data-driven decision-making. Special attention is given to the Jobs to Be Done (JTBD) framework as a strategic tool for aligning products and services with customer needs. The study also explores the impact of digital transformation on operational agility, emphasizing the importance of adaptability, automation, and efficient resource allocation. Furthermore, it discusses how digital tools contribute to employee engagement, collaboration, and professional development, fostering a culture of innovation. In addition, the paper analyzes the application of digital transformation in healthcare, demonstrating its role in improving patient care, accessibility, and decision-making. Overall, the research concludes that a well-implemented digital transformation strategy significantly enhances organizational performance, competitiveness, and customer experience.